Алгоритм обработки данных измерения концентрации методом хроноионометрии - Суровцев, И.В.; Галимов, С.К. (Управляющие системы и машины, 2016)
Предложен алгоритм обработки данных измерения концентрации химических элементов методом хроноионометрии при помощи ионоселективных электродов и нового хлорсеребряного электрода с двойным электролитическим ключом на приборе инверсионной хронопотенциометрии. Запропоновано алгоритм обробки даних вимірювання концентрації хімічних елементів методом хроноіонометрії за допомогою іонселективних електродів та нового хлорсрібного електроду з подвійним електролітичним ключем на приладі інверсійної хронопотенціометрії. Introduction. The method of the repeated additive using the actual inclination of electrode function is the most exact at concentration measurement of the elements in ionometry. Purpose. The purpose of research is to create the data processing algorithm of measurement concentration on the device of inversion chronopotentiometry with the ion-selective electrodes use and a method of the repeated additive. Methods. According to the algorithm, values are read out on the device at a rate of 4 kHz, the magnitude of the potential is determined in a cycle of measurement by duration 1 second and the graph of chronopotentiogram is displayed for the control of stability. The mass of an element in a solution of sample is found out of linear relationship of the potential difference from the logarithm mass of additives, values of additives are defined more precisely and value of element concentration is determined under the electrode characteristic of the additive. Results. The new method of chronoionometry which uses the algorithm for concentration measurement on the device of inversion chronopotentiometry is created. It is successfully applied at creation of methods of measurement performance of potassium, sodium and calcium in drinking and natural water mass concentration without preparation of the sample that substantially augments rapidity and simplicity of carrying out the analysis. New developed chlorine-silver electrode with double electrolytic key which is applied in methods has confirmed the own capacity for work and reliability. Conclusion. The suggested algorithm improves presentation and the stability control of potentials measurement, allows the user to choose the concrete values of the additives potentials at calculation of the concentration that augments the reliability and accuracy of concentration measurement, expands functionalities of the device and makes it more universal.